Spaghetti Shakespeare: „Johnny Hamlet” and the Italian Western - Ciraulo, Darlena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
The Italian Western, Johnny Hamlet (1968), directed by Enzo G. Castellari, draws on the revenge story of Shakespeare’s tragedy Hamlet for plot and characterization. While international distributors of the film downplayed its connection to highbrow Shakespeare, they emphasized the movie’s violent content and actionpacked revenge narrative, which was typical of the western all’italiana. Johnny Hamlet shares similarities with the brutally violent Django (1966), directed by Sergio Corbucci, whose avenging angel protagonist epitomizes the Spaghetti Western antihero. Although the filmmakers of Johnny Hamlet characterized Johnny as a vindicator, they also sought to develop the “broody” aspect of this gunfighter, one based on Shakespeare’s famously ruminating hero. Using innovative film techniques, Johnny Hamlet shows Johnny as a contemplative pistolero.